A novel lncRNA DFRV plays a dual function in influenza A virus infection - Wang, Keyu; Gong, Meiliang; Zhao, Sumin; Lai, Chengcai; Zhao, Lingna; Cheng, Sijie; Xia, Min; Li, Yuru; Wang, Kun; Sun, Heqiang; Zhu, Pingjun; Zhou, Yu; et al. (Frontiers in Microbiology, 2023)
Long noncoding RNAs (lncRNAs) have been associated with a variety of biological activities, including immune responses. However, the function of lncRNAs in antiviral innate immune responses are not fully understood. Here, we identified a novel lncRNA, termed DFRV(dual function regulating influenza virus), elevating in a dose- and time-dependent manner during influenza A virus (IAV) infection, which was dependent on the NFκB signaling pathway. Meanwhile, DFRV was spliced into two transcripts post IAV infection, in which DFRV long suppress the viral replication while DFRV short plays the opposite role. Moreover, DFRV regulates IL-1β and TNF-α via activating several pro-inflammatory signaling cascades, including NFκB, STAT3, PI3K, AKT, ERK1/2, JNK and p38. Besides, DFRV short can inhibit DFRV long expression. Collectively, our studies reveal that DFRV may act as a potential dual-regulator to preserve innate immune homeostasis in IAV infection.